Polar super seaways? : maritime transport in the Arctic : an analysis of shipowners’ intentions - Lasserre, Frédéric; Pelletier, Sébastien (Journal of Transport Geography, 2016)
The seasonal melting of sea ice in the Arctic Ocean, which has been confirmed for several summers in a row and is widely documented, has become a hot topic in the media. It is fuelling many speculative scenarios about the purported renewal of a “cold war”, or even an actual armed conflict, in the Arctic, for the control of both its natural resources and its sea routes. The melting sea ice is indeed giving a second wind to projects, abandoned in the 19th century, to find shorter sea routes between Europe and Asia. A look at the map shows the savings in distance that can be achieved with the Arctic routes: for example, a trip between London and Yokohama through the Northwest Passage is 15,700 km and 13,841 km through the Northeast Passage, which is significantly shorter than the route through Suez (21,200 km) or Panama (23,300 km).2 These findings fuel the idea that these Arctic routes, because they are shorter, are bound to attract abundant through traffic, and consequently will become a major political issue. Amid the media widespread image of a future maritime highway across Arctic seas, even some scientists yield to the popular image and assert, without proof, that Arctic traffic is set to increase rapidly.3 Beyond the seemingly decisive advantage of Arctic routes, however, there remain many obstacles to navigation (Lasserre, 2010d). In addition, these scenarios for the development of marine traffic in the Arctic remain highly speculative and are not based on an analysis of shipowners’ perceptions, which is the goal of this paper. This article will thus present the results of an empirical survey conducted among shipping companies to determine their interest in developing activities in the Arctic. Besides examining the potential development of shipping in Arctic routes, this research must be replaced in the context of intense competition between shippers, competition that makes both service reliability and costs of transport paramount. In this competition structure, the benefits of established routes between ...